2015
DOI: 10.21070/nabatia.v12i1.1596
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Arbuscular Vesicular Mycorrhizae on the Efficiency of Phosphate Absorption on the Growth and Production of Cayenne Pepper (Capsicum Frutescens L. )

Abstract: This study aims to determine the effect of vesicular arbuscular mycorrhiza and phosphate fertilization on the growth and production of cayenne pepper (Capsicum frutescens L. ). Research conducted at the Greenhouse o f Faculty of Agriculture, University of Muhammadiyah Sidoarjo. Factorial experiment arranged in a completely randomized design (CRD) with repeat 4 times. The first factor: VA mycorrhizal (with and without mycorrhiza); the second factor: phosphate (0, 100, 200 and 300 kg TSP/Ha). The variables measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The findings suggest that grape polyphenols have potential prebiotic effects on modulating the gut microbiota composition and generating SCFAs that contribute to the improvements of host health. M Abror, et al [102] concluded that leri water and lactobacillus bacteria have an effect on the growth and production of mustard greens.…”
Section: Present Status Of Natural Association Of Human Gut Microbes ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings suggest that grape polyphenols have potential prebiotic effects on modulating the gut microbiota composition and generating SCFAs that contribute to the improvements of host health. M Abror, et al [102] concluded that leri water and lactobacillus bacteria have an effect on the growth and production of mustard greens.…”
Section: Present Status Of Natural Association Of Human Gut Microbes ...mentioning
confidence: 99%
“…It is evident that some of the gut microbes are associated with the crop plants in the agricultural production system with some unknown and known roles (Mundt, et al [110,111,103,109,114,113,100,102]) . These gut microbes are indispensable part of the human health and their population and equilibrium in the gut plays an important role in various metabolic, hormonal, and neurological functions.…”
Section: Concept Of Human Gut Microbe Assisted Agricultural Food Prod...mentioning
confidence: 99%
“…Phytohormones consisting of a mixture of coconut water, bean sprouts and bamboo shoots, which contain the hormones auxin, cytokinins and gibberellins (Purdyaningsih, 2013). The auxin phytohormone contained in bean sprouts can help accelerate and support the vegetative period of plants so that they enter the generative period more quickly (Miftakurrohmat & Dewantara, 2020). Optimum administration of auxin can increase meristematic cell division, and this increase in cell division can accelerate plant growth, especially plant height (Khairuna, 2019).…”
Section: Figure 1 Comparison Of Plant Heightmentioning
confidence: 99%
“…Optimum administration of auxin can increase meristematic cell division, and this increase in cell division can accelerate plant growth, especially plant height (Khairuna, 2019). Likewise, the provision of cytokinin phytohormones contained in coconut water has benefits in increasing plant growth (Miftakurrohmat & Dewantara, 2020).…”
Section: Figure 1 Comparison Of Plant Heightmentioning
confidence: 99%